Alpha-lipoic Acid suppresses P2X receptor activities and visceral hypersensitivity to colorectal distention in diabetic rats - Ji Hu (Nature Portfolio, 2017)
Abstract The present study was designed to investigate the roles of P2X3 receptors in dorsal root ganglion (DRG) neurons in colonic hypersensitivity and the effects of alpha-lipoic acid (ALA) on P2X3 receptor activity and colonic hypersensitivity of diabetic rats. Streptozotocin (STZ) was used to induce diabetic model. Abdominal withdrawal reflex (AWR) responding to colorectal distention (CRD) was recorded as colonic sensitivity. ATP-induced current density of colon-specific DRG (T13-L2 DRGs) neurons was measured with whole-cell patch clamp. The expression of P2X3Rs of T13-L2 DRGs was measured by western blot analysis. The results showed that AWR scores significantly increased after STZ injection. P2X3R expression and ATP current density of T13-L2 DRG neurons were enhanced in diabetic rats. Intraperitoneal injection with ALA once a day for 1 week remarkably reduced P2X3R expression and ATP current density in diabetic rats. Importantly, ALA treatment attenuated colonic hypersensitivity in diabetic rats. Our data suggest that STZ injection increases expression and function of P2X3 receptors of colon-specific DRG neurons, thus contributing to colonic hypersensitivity in diabetic rats. Administration of ALA attenuates diabetic colonic hypersensitivity, which is most likely mediated by suppressing expression and function of P2X3 receptors in DRGs of diabetic rats.